Bioconversion of palm oil mill effluent for citric acid production: statistical optimization of fermentation media and time by central composite design - Alam, Md. Zahangir; Jamal, Parveen; M. Nadzir, Masrina (Springer Science, 2008)
A laboratory-scale study was conducted to evaluate the feasibility of using palm oil mill effluent (POME) as a major substrate and other nutrients for maximum production of citric acid using the potential fungal strain Aspergillus niger (A103). Statistical optimization of medium composition (substrate–POME,co-substrates–wheat flour and glucose, and nitrogen source–ammonium nitrate) and fermentation time was carried out by central composite design (CCD) to develop a polynomial regression model through the effects of linear,quadratic, and interaction of the factors. The statistical analysis of the results showed that, in the range studied, ammonium nitrate had no significant effect whereas substrate,co-substrates and fermentation time had significant effects on citric acid production. The optimized medium containing 2% (w/w) of substrate concentration (POME), 4% (w/w) of wheat flour concentration, 4% (w/w) of glucose concentration, 0% (w/v) of ammonium nitrate and 5 days fermentation time gave the maximum predicted citric acid of 5.37 g/l which was found to be 1.5 g/l in the experimental run. The determination of coefficient (R2) from the analysis observed was 0.964, indicating a satisfactory adjustment of the model with the response. The analysis showed that the major substrate POME (P\0.05), glucose (P\0.01), nutrient (P\0.05), and fermentation time (P\0.01) was more significant for citric acid production. The bioconversion of POME for citric acid production using optimal conditions showed the higher removal of chemical oxygen demand (82%) with the production of citric acid (5.2 g/l) on the final day of fermentation process (7 days). The pH and biosolids accumulation were observed during the bioconversion process.